Effects of Proton Pump Inhibitors and H2 Receptor Antagonists on the Ileum Motility - Atilla Kurt; Ahmet Altun; Ihsan Bagcivan; Ayhan Koyuncu; Omer Topcu; Cengiz Aydin; Tijen Kaya (Gastroenterology Research and Practice)
Objectives. To investigate the effects of proton pump inhibitors (PPIs) and H2 receptor antagonists on ileum motility in rats with peritonitis and compare changes with control group rats. Methods. Peritonitis was induced by cecal ligation and puncture in 8 rats. Another of 8 rats underwent a sham operation and were accepted as controls. Twenty-four hours later after the operation, the rats were killed, and their ileum smooth muscle was excised and placed in circular muscle direction in a 10 mL organ bath. Changes in amplitude and frequency of contractions were analyzed before and after PPIs and H2 receptor blockers. Results. PPI agents decreased the motility in a dose-dependent manner in ileum in both control and intraabdominal sepsis groups. While famotidine had no significant effect on ileum motility, ranitidine and nizatidine enhanced motility in ileum in both control and intraabdominal sepsis groups. This excitatory effect of H2 receptor antagonists and inhibitor effects of PPIs were significantly high in control group when compared to the peritonitis group. The inhibitor effect of pantoprazole on ileum motility was significantly higher than the other two PPI agents. Conclusions. It was concluded that H2 receptor antagonists may be more effective than PPIs for recovering the bowel motility in the intraabdominal sepsis situation.